PENINGKATKAN KEAKTIFAN PESERTA DIDIK DENGAN MAKE A MATCH PADA PEMBELAJARAN MATEMATIKA KELAS II SD - Ida Nur Hafsah (Program Studi PGSD STKIP PGRI Banjarmasin, 2023)
The purpose of this research is to analyze how the use of Make A Match can increase student activity. The method used is descriptive quantitative. This type of research describes or presents data that has been collected as it is for analysis. The data that the researchers used were primary data, namely observation sheets/observations during the teaching and learning process that were related to the implementation of Mathematics learning material in units of time (hours, weeks, months, years) using Make A Match. Presentation of data in the form of graphs. This research was conducted at SD Negeri 1 Wonosegoro with 26 grade 2 students consisting of 14 boys and 12 girls. The result of the research is that students are actively involved during the learning process. Based on observations during the course of learning using observation instruments, it shows that students' active involvement in the learning process is 85% in the good category. 11% in the sufficient category and 4% in the category of needing guidance. In succession the number of students in the good, sufficient, and needing guidance categories is 22 people in the good category, 3 people in the sufficient category and 1 person needs guidance. 22 students seemed to be actively involved. So that learning objectives that are fun and student-centered can be realized.